Analisis Neraca Air Lahan terhadap Jenis Tanah yang Berkembang pada Daerah Karts di Kecamatan Parigi Kabupaten Muna Sulawesi Tenggara - M Tufaila; La Mpia; Jufri Karim (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
Soil water balance is describes the condition of the water in an area. The difference of climatic conditions and land characteristic denotes the effect of the soil water balance. The objective of this study is to determine soil water balance on the type of soil that developed at parent material karts. Village Parigi district Muna has an area of 16245.88 ha consists of Inceptisol, Mollisol, and Andosol and developing in Qal and Qpw geological formation. The results of research showed that surplus on rainwater occurred in February, March, and April. While the water deficit occurred in January, May, June, July, August, September, October, November, and December. Soil water balance in the research site was affected by climate, soil condition, and soil characteristic. Soil was formed above the karst rock showing little effect on the soil water balance. ABSTRAK Neraca air lahan menggambarkan kondisi air pada suatu wilayah. Perbedaan kondisi iklim dan karateristik lahan memberikan pengaruh terhadap nerca air lahan. Tujuan penelitiaan ini yaitu untuk mengetahui neraca air lahan pada jenis tanah yang berkembang pada bahan induk karts. Kecamatan Parigi Kabupaten Muna memiliki luas 16.245,88 ha terdiri dari jenis tanah Iceptisol, Mollisol, dan Andisol dan berkembang pada formasi geologi Qal dan Qpw. Hasil penelitiaan menunjukan bahwa surpulus air hujan terjadi pada bulan Februari, Maret dan April, sedangkan divisit air terjadi pada bulan Januari, Mei, Juni, Juli, Agustus, September, Oktober, November, dan Desember. Neraca air lahan dilokasi penelitian dipengaruhi oleh iklim, kondisi lahan, dan karateristik tanah. Tanah yang terbentuk diatas batuan karts memberikan pengaruh yang kecil terhadap neraca air lahan.